Advances in mass spectrometry-based cancer research and analysis: from cancer proteomics to clinical diagnostics. (2nd June 2016) - Timms, John F.; Hale, Oliver J.; Cramer, Rainer
ABSTRACT: Introduction : The last 20 years have seen significant improvements in the analytical capabilities of biological mass spectrometry (MS). Studies using advanced MS have resulted in new insights into cell biology and the etiology of diseases as well as its use in clinical applications. Areas covered : This review discusses recent developments in MS-based technologies and their cancer-related applications with a focus on proteomics. It also discusses the issues around translating the research findings to the clinic and provides an outline of where the field is moving. Expert commentary : Proteomics has been problematic to adapt for the clinical setting. However, MS-based techniques continue to demonstrate potential in novel clinical uses beyond classical cancer proteomics.